2008
DOI: 10.1373/clinchem.2008.109603
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MicroRNAs in Pancreatic Fine-Needle Aspirates Can Classify Benign and Malignant Tissues

Abstract: BACKGROUND MicroRNAs (miRNAs) are RNA molecules that are involved in the regulation of many cellular processes, including those related to human cancers. The aim of this study was to determine, as a proof of principle, whether specific candidate miRNAs could be detected in fine-needle aspirate (FNA) biopsies of pancreatic ductal adenocarcinoma (PDAC) and could accurately differentiate malignant from benign pancreatic tissues. METHODS We used TaqMan® assays to quantify miRNA levels in FNA samples collected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
185
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(197 citation statements)
references
References 37 publications
9
185
3
Order By: Relevance
“…Nine of the significantly differentially expressed miRNAs described by Bloomston et al 20 were also found in our study (miR-21, miR-100*, miR-143/miR-143*, miR-148a, miR-148a*, miR-205, miR-210, miR-222 and miR-375). Eleven of the significantly differentially expressed miRNAs described by Szafranska et al 21,26 were found in our study with very similar dm-values and fold change (miR-31, miR-130b, miR-143/miR-143*, miR-148a, miR-196b, miR-205, miR-210, miR-216, miR-217, miR-222/miR-222* and miR-375).…”
Section: Pancreatic Adenocarcinomas Vs Normal Pancreassupporting
confidence: 84%
See 4 more Smart Citations
“…Nine of the significantly differentially expressed miRNAs described by Bloomston et al 20 were also found in our study (miR-21, miR-100*, miR-143/miR-143*, miR-148a, miR-148a*, miR-205, miR-210, miR-222 and miR-375). Eleven of the significantly differentially expressed miRNAs described by Szafranska et al 21,26 were found in our study with very similar dm-values and fold change (miR-31, miR-130b, miR-143/miR-143*, miR-148a, miR-196b, miR-205, miR-210, miR-216, miR-217, miR-222/miR-222* and miR-375).…”
Section: Pancreatic Adenocarcinomas Vs Normal Pancreassupporting
confidence: 84%
“…All miRNAs either up-or down-regulated compared with normal pancreas in other studies 20,21,26 were also significantly differentially expressed in our study before the strict Bonferonni correction for multiple comparisons, except miR-155 that was not present in our microRNA array (Table 2).…”
Section: Pancreatic Adenocarcinomas Vs Normal Pancreassupporting
confidence: 56%
See 3 more Smart Citations